CAPACITY OF SUNTER C RIVER IN NORTH JAKARTA - Mohammad Imamuddin; Muhammad Lutfi Fadilah (University Of Muhammadiyah Jakarta, 2021)
Sunter C river is located on Yos Sudarso street at coordinates 6°8'32,63